Guidelines for preoperative visual function and imaging examination standards in vitreoretinal surgery (2025) - Yi Shao; Jian Ma; Zhao-Yang Wang; Expert Workgroup of Guidelines for Preoperative Visual Function and Imaging Examination Standards in Vitreoretinal Surgery (2025); Ophthalmic Imaging and Intelligent Medicine Branch Chinese Medicine Education Association; Ophthalmology Committee of International Association of Translational Medicine; Ophthalmology Committee of International Association of Intelligent Medicine (International Journal of Ophthalmology)
This guideline seeks to thoroughly investigate the standardized operational procedures for visual function and imaging examinations prior to vitreoretinal surgery. Preoperative assessments can greatly assist clinicians in determining surgical indications, assessing patient conditions, and offering valuable assistance in formulating surgical strategies and predicting outcomes. Developed by a collaborative team of experts from the Ophthalmic Imaging and Intelligent Medicine Branch of the Chinese Medical Education Association, in conjunction with the Ophthalmic Imaging and Intelligent Medicine Branch of the Chinese Medical Education Association, these guidelines have been formulated through extensive research and evaluation, incorporating the latest technological advancements and studies on a global and domestic scale in vitreoretinal surgery. After extensive deliberations and incorporation of up-to-date clinical data, these guidelines have been developed to assist in standardizing preoperative examinations for vitreoretinal surgery. The overarching goals include improving medical quality, maximizing resource allocation, offering decision-making assistance, and safeguarding patient rights. This document provides a comprehensive analysis of preoperative assessments for vitreoretinal procedures, covering principles, methodologies, and precautions related to a range of diagnostic techniques including ultra-wide-angle fundus imaging, fluorescein angiography, indocyanine green angiography, ophthalmic B-ultrasound examinations, ultrasound biomicroscopy, optical coherence tomography, optical coherence tomography angiography, orbital CT scan, orbital MRI, and ophthalmic electrophysiology tests such as electroretinograms, visually evoked potentials, and visual field testing.